2018
DOI: 10.3389/fpls.2018.01272
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Mapping of Seedling Heat Tolerance in Winter Wheat

Abstract: Heat stress during the seedling stage of early-planted winter wheat (Triticum aestivum L.) is one of the most abiotic stresses of the crop restricting forage and grain production in the Southern Plains of the United States. To map quantitative trait loci (QTLs) and identify single-nucleotide polymorphism (SNP) markers associated with seedling heat tolerance, a genome-wide association mapping study (GWAS) was conducted using 200 diverse representative lines of the hard red winter wheat association mapping panel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
88
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(103 citation statements)
references
References 60 publications
(77 reference statements)
6
88
0
Order By: Relevance
“…Through association analysis, markers have been used to identify the QTLs/genes linked with economically important traits [85]. Association analysis has been clearly comprehended in cereals such as wheat [127,128], maize [129], barley [130], and sorghum [131]. In winter wheat, QTLs and markers associated with seedling heat tolerance was studied which is useful for early planting and dual-purpose wheat breeding in United States [128].…”
Section: Genomic Regions Linked To Heat Tolerancementioning
confidence: 99%
See 1 more Smart Citation
“…Through association analysis, markers have been used to identify the QTLs/genes linked with economically important traits [85]. Association analysis has been clearly comprehended in cereals such as wheat [127,128], maize [129], barley [130], and sorghum [131]. In winter wheat, QTLs and markers associated with seedling heat tolerance was studied which is useful for early planting and dual-purpose wheat breeding in United States [128].…”
Section: Genomic Regions Linked To Heat Tolerancementioning
confidence: 99%
“…Association analysis has been clearly comprehended in cereals such as wheat [127,128], maize [129], barley [130], and sorghum [131]. In winter wheat, QTLs and markers associated with seedling heat tolerance was studied which is useful for early planting and dual-purpose wheat breeding in United States [128]. In legumes, very limited reports are available for association studies particularly under abiotic stress.…”
Section: Genomic Regions Linked To Heat Tolerancementioning
confidence: 99%
“…Several studies found that the combination of drought and heat stress had greater negative effect on the productivity of crops compared with each of the different stresses applied individually (Prasad, Pisipati, Momcilovic, & Ristic, ). To date, various QTL/alleles responding to drought or heat stress were detected in wheat (Kulkarni et al, ; Maulana et al, ), whereas studies of the genetic basis of responses to combined drought and heat stress are rare (Liu et al, ). Previous studies revealed that the responses of plants to a combined abiotic stresses are unique and cannot be directly predicted from the plant performance under different stresses individually (Suzuki, Rivero, Shulaev, Blumwald, & Mittler, ), and most of the transcriptome changes responding to combined heat and drought stress differ from that under individual stressor (Sakuma et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, QTLs for heat tolerance during the vegetative or the grain-filling stage have been discovered [32,39,40]. Recently, a QTL study for seedling heat tolerance was conducted under controlled growth chamber conditions using winter wheat cultivars collected across the Great Plains of the United States [41]. This study detected multiple QTLs in different chromosomes spreading across the wheat genome [41].…”
Section: Improving Traits Of Wheat Cultivars Desirable For Dual-purpomentioning
confidence: 98%
“…Recently, a QTL study for seedling heat tolerance was conducted under controlled growth chamber conditions using winter wheat cultivars collected across the Great Plains of the United States [41]. This study detected multiple QTLs in different chromosomes spreading across the wheat genome [41]. The molecular markers identified to date will facilitate the selection of seedling drought and heat tolerance during dual-purpose wheat breeding.…”
Section: Improving Traits Of Wheat Cultivars Desirable For Dual-purpomentioning
confidence: 99%